Genital endometriosis as a cause of female infertility - O.S. Zakharenko; О.M. Yuzko; L.V. Zakharenko (Bukovynian State Medical University, 2013)
Cited data review of literature in relation to the role of external genital endometriosis in the structure of gynaecological morbidity in a reproductive period and tactician of treatment of the sterility associated with a genital endometriosis.